A lithium slag-based composite gelling material and preparation method thereof
Through the activation treatment of lithium slag and inorganic acid solution and the mechanical mixing of alkaline substances, combined with the addition of appropriate amounts of auxiliary materials, the problems of low compressive strength and high preparation cost of lithium slag gelling materials are solved, and high efficiency and low cost lithium is achieved Preparation of slag-based composite cementitious materials can replace high-grade cement.
Patent Information
- Application Number
- CN202411587117.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-08
AI Technical Summary
In the prior art, when using lithium slag to prepare gelling materials, a large amount of excitants and auxiliary materials are required to add, resulting in high preparation cost and low compressive strength, which cannot replace cement.
By mixing lithium slag with inorganic acid solution for activation treatment, active aluminates and silicates are generated and mechanically mixed with alkaline substances, further promoting the deep dissociation of aluminosilicates and reducing dependence on the exciters. At the same time, add appropriate amount of auxiliary materials such as fly ash and gypsum to achieve high compressive strength of lithium slag-based composite gelling materials.
The high compressive strength of lithium slag-based composite cementitious material is achieved, and the cost is low. It can replace 52.5 or even 62.5 cement, and avoid the consumption of alkali triggers, reduce the amount of clinker and cement, and shorten the process flow.
Smart Images

Figure CN119080410B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of composite materials, and in particular to a lithium slag-based composite cementitious material and a preparation method thereof. Background Art
[0002] Lithium slag is produced when lithium ores such as lepidolite and spodumene are used to extract lithium salt products. Lithium slag is not only difficult to dispose of, but also easily causes major pollution accidents. However, lithium slag is rich in elements such as aluminum, silicon, and calcium, and is mainly present in the form of calcium feldspar and glass. Therefore, it can be used as an important raw material for the preparation of cementitious materials.
[0003] At present, when lithium slag is used to prepare cementitious materials, not only a large amount of activator is required to activate the reaction activity of lithium slag, but also a large amount of auxiliary materials are required. This leads to a high preparation cost of cementitious materials, and the compressive strength of the prepared cementitious materials is not high, and it cannot replace cement. Summary of the invention
[0004] The embodiment of the present application provides a lithium slag-based composite gelling material and a preparation method thereof. The preparation method of the present application has low cost, and the prepared lithium slag-based composite gelling material also has high compressive strength.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a lithium slag-based composite cementitious material, which comprises the following steps: S100, mixing lithium slag with an inorganic acid solution and performing an activation treatment to obtain an activated material, wherein the components of the lithium slag include aluminosilicate and calcium oxide; S200, mechanically mixing an alkaline substance and the activated material to obtain a modified material, wherein the pH of the modified material is 7 to 10, and then drying the modified material to obtain a modified powder; S300, grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material.
[0006] In the preparation method of the present application, the inventors found that in step S100, the lithium slag and the inorganic acid solution are mixed and then activated. The inorganic acid solution can react with the lithium slag to activate and depolymerize the inert aluminosilicate to generate active aluminates and silicates, which can improve the volcanic ash activity of the lithium slag. Moreover, the impurity elements such as aluminum and calcium in the lithium slag can also be used as retarders and stimulants in situ at this time, and the reaction activity of the lithium slag can be improved without adding additional stimulants. After obtaining the powdered activated material, the activated material and the alkaline substance are mixed in step S200. On the one hand, the alkaline substance can neutralize the excess hydrogen ions in the activated material, so that the modified material produced is neutral or weakly alkaline as a whole; on the other hand, the alkaline substance can further promote the deep dissociation of aluminosilicates. Therefore, the addition of alkaline substances in step S200 can improve the stability of the gelling system on the one hand, and can further improve the reaction of the lithium slag on the other hand. Finally, the auxiliary materials and the modified materials formed after drying are ground. Since the elements such as aluminum, silicon, sulfur, and calcium in the system have been induced and excited, the reaction activity of the modified materials is relatively high. Therefore, a lithium slag-based composite cementitious material with high compressive strength can be generated without adding a large amount of auxiliary materials.
[0007] In a possible implementation, based on the mass of lithium slag, the mass content of aluminum oxide in the aluminosilicate is 10% to 20%, the mass content of silicon dioxide in the aluminosilicate is 30% to 60%, and the mass content of calcium oxide is 5% to 30%.
[0008] In a possible implementation, the lithium slag includes at least one of lepidolite smelting slag or spodumene smelting slag.
[0009] In the above technical solution, the lithium slag can be either lepidolite smelting slag or spodumene smelting slag, which is beneficial to environmental protection.
[0010] In a possible implementation, the method for preparing a lithium slag-based composite cementitious material satisfies at least one of the following conditions: (1) the inorganic acid in the inorganic acid solution includes at least one of sulfuric acid or nitric acid; (2) the hydrogen ion concentration of the inorganic acid solution is 5 mol / L to 36 mol / L; (3) the mass of the inorganic acid solution accounts for 5% to 20% of the mass of the lithium slag.
[0011] In the above technical solution, the inorganic acid solution can well activate the lithium slag, making the lithium slag more active, which is more conducive to preparing a lithium slag-based composite cementitious material with high compressive strength.
[0012] In a possible implementation, a mechanical activation method is used for the activation treatment.
[0013] In the above technical solution, the mechanical activation method can be used to fully mix the lithium slag and the inorganic acid solution, which is beneficial to further improve the reaction activity of the lithium slag.
[0014] In a possible implementation, the alkaline substance includes at least one of carbide slag, steel slag, magnesium slag, calcium hydroxide or sodium hydroxide.
[0015] In a possible implementation, the step of mechanically mixing the alkaline substance and the activated material includes a first mechanical mixing and a second mechanical mixing in sequence; the rotation speed of the first mechanical mixing is 100r / min~200r / min, the time is 60min~90min, and the mass of the added alkaline substance accounts for 5%~20% of the mass of the lithium slag; the rotation speed of the second mechanical mixing is 250r / min~400r / min, the time is 30min~60min, and the mass of the added alkaline substance accounts for 2%~4% of the mass of the lithium slag.
[0016] In the above technical scheme, the first mechanical mixing process can neutralize the excess proton acid, making the mixture neutral or weakly alkaline, and can also generate mineral phases such as calcium sulfate and aluminum sulfate, providing active raw materials for the subsequent generation of gelled mineral phases such as calcium sulfonate and hydrated calcium silicate; the second mechanical mixing process can further decompose the undissociated aluminosilicates in the lithium slag to generate active aluminates and silicates, further improve the activity of the modified lithium slag, increase the lithium slag dosage, and avoid consuming the activator generated during the activation treatment.
[0017] In a possible implementation, the auxiliary material includes at least one of slag, clinker, fly ash or gypsum; and / or the mass of the added auxiliary material accounts for 40% to 60% of the mass of the lithium slag.
[0018] In the above technical solution, the mass of the added auxiliary materials is relatively small, which can well reduce the preparation cost without affecting the compressive strength of the product.
[0019] In a possible implementation, the method for preparing the lithium slag-based composite cementitious material satisfies at least one of the following conditions: (1) the gypsum includes at least one of desulfurized gypsum, anhydrite, phosphogypsum or fluorite; (2) the fly ash includes at least one of fluidized bed fly ash or pulverized coal furnace fly ash; (3) the clinker includes at least one of silicate clinker, aluminate clinker or sulphoaluminate clinker.
[0020] In a second aspect, the present application provides a lithium slag-based composite gelling material, which is prepared by the above-mentioned method for preparing the lithium slag-based composite gelling material.
[0021] In the above technical solution, the obtained lithium slag-based composite cementitious material has high compressive strength, and its compressive strength conforms to the corresponding regression equation, and the required mechanical properties can be obtained by adjusting the material parameters.
[0022] The beneficial effects of this application are:
[0023] In the preparation method provided in the present application, lithium slag is used as a raw material, and proton acid activation and mechanical coupling are adopted to achieve depolymerization and activation of inert aluminosilicates to generate active aluminates and silicates, which not only improves the volcanic ash activity of the lithium slag, but also the aluminum and calcium impurity elements can be used in situ to form aluminum-calcium chemical activators, solving the problem of low reaction activity of lithium slag; by adding calcium-based solid waste in batches, on the one hand, the stability of the gelling system is ensured by neutralizing excess sulfuric acid, and on the other hand, the deep dissociation of aluminosilicates is further promoted to improve the activity, so as to achieve stability of the gelling system and greatly improve the activity of lithium slag; finally, by adding fly ash, gypsum, slag and clinker in batches, the system is induced to generate gelling materials by elements such as aluminum, silicon, sulfur and calcium. The obtained lithium slag-based composite gelling material can meet the requirements of 52.5 or even 62.5 cement grades according to standard tests, while avoiding the consumption of alkali activators, greatly reducing the amount of clinker and cement, shortening the process flow and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a process flow chart of an embodiment of the present application. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] At present, the lithium slag produced in the process of extracting lithium from special lithium ores such as lepidolite / spodumene can be used as an important material for cementitious materials. For example, CN117756487B discloses a lithium slag cementitious material and a preparation method thereof, wherein lithium slag is mixed with cement to obtain a lithium slag cementitious material. CN106116189B also discloses a method for preparing a clinker-free lithium slag composite cementitious material. However, in the current process of preparing cementitious materials, a large amount of activator is often required to be added to activate the lithium slag, and a large amount of auxiliary materials are also required, which results in a high preparation cost of the cementitious material, and the compressive strength of the obtained cementitious material is not high, and it cannot replace cement.
[0028] In order to improve the above technical problems, the present application provides a lithium slag-based composite cementitious material and a preparation method thereof. The contents of the present application are described in detail below.
[0029] The process flow chart of the preparation method of the lithium slag-based composite gelling material of the present application is as follows Figure 1 As shown, it includes the following steps:
[0030] S100, mixing lithium slag with an inorganic acid solution and performing activation treatment to obtain an activated material, wherein the components of the lithium slag include aluminosilicate and calcium oxide.
[0031] In this step, when the lithium slag is mixed with the inorganic acid and then activated, the inorganic acid solution can react with the lithium slag, so that the inert aluminosilicate is activated and depolymerized to generate active aluminates and silicates, which can improve the volcanic ash activity of the lithium slag, and the aluminum-calcium impurities in the lithium slag can be used as retarders and stimulants in situ, and the reaction activity of the lithium slag can be improved without the need to add additional stimulants; therefore, the activated material obtained in this step is a powder with good reaction activity. Moreover, in this step, the acid in the acid solution is generally an inorganic acid, because the organic acid will not be completely ionized in water, and the organic groups in the solution will have an adverse effect on the compressive strength and service life of the obtained product. Specifically, the acid in the inorganic acid solution is generally an industrial by-product inorganic acid, which can be at least one of hydrogen chloride, sulfuric acid or nitric acid. However, in the actual operation process, since hydrogen chloride contains chloride ions, it will have an adverse effect on the compressive strength and service life of the obtained product, so at least one of sulfuric acid and nitric acid is usually selected. In addition, the concentration of hydrogen ions in the inorganic acid solution is generally not less than 5 mol / L, otherwise it is not easy to activate the lithium slag; the maximum concentration of hydrogen ions generally does not exceed 36 mol / L. In addition, the mass of the inorganic acid solution generally accounts for 5% to 20% of the mass of the lithium slag, for example, it can be 5%, 8%, 10%, 15%, 20%, etc. or within the range of any two of the above values.
[0032] The molecular formula of aluminosilicate in lithium slag can be expressed as xAl 2 O 3 ySiO 2In some embodiments of the present application, the content of aluminum oxide is usually 10% to 20% by mass of lithium slag, and can be specifically 10%, 12%, 15%, 20%, etc., or within the range of any two of the above values, and the content of silicon dioxide is usually 30% to 60%, and can be specifically 30%, 40%, 50%, 60%, etc., or within the range of any two of the above values; In addition, in the present application, the content of calcium oxide is usually between 5% and 30% by mass of lithium slag, and can be specifically 5%, 10%, 15%, 20%, 25%, 30%, etc., or within the range of any two of the above values. The type of lithium slag is usually at least one of lithium mica smelting slag or spodumene smelting slag. As an example, in the embodiments of the present application, the lithium slag is all from the same batch, and the lithium slag has an aluminum oxide content of 12%, a silicon dioxide content of 40%, and a calcium oxide content of 25% by mass fraction. In addition, in actual production, the components of lithium slag, in addition to alumina and silicon dioxide, generally include 5% to 25% of other components such as sulfur trioxide. Taking sulfur trioxide as an example, sulfur trioxide can promote the formation of calcium sulfoxide cementitious minerals, thereby improving its compressive strength. In this application, the content of sulfur trioxide is 18%.
[0033] In addition, in some embodiments of the present application, this step generally involves gradually adding an inorganic acid solution to the lithium slag and mixing it evenly, which is conducive to fully improving the activity of the lithium slag. The activation treatment generally adopts a mechanical activation method, and the equipment used includes at least one of a ball mill, a vertical mill, a mixer, a rod mill or a column mill. Moreover, during the activation treatment, it usually includes a first activation stage treatment and a second activation stage treatment, which can make the reaction activity of the lithium slag higher. During the first activation stage, the rotation speed is 50r / min~150r / min, and the grinding time is 30min~60min; for example, during the first activation stage, the rotation speed can be 50r / min, 70r / min, 90r / min, 110r / min, 130r / min, 150r / min, etc. or within the range of any two of the above values, and the grinding time can be 30min, 40min, 50min, 60min, etc. or within the range of any two of the above values; during the second activation stage, the rotation speed is 250r / min~400r / min, and the time is 30min~90min, for example, during the second activation stage, the rotation speed can be 250r / min, 300r / min, 350r / min, 400r / min, etc. or within the range of any two of the above values, and the grinding time can be 30min, 50min, 70min, 90min, etc. or within the range of any two of the above values.
[0034] S200, mechanically mixing the alkaline substance and the activated material to obtain a modified material, the pH of the modified material is 7-10, and then drying the modified material to obtain a modified powder.
[0035] This step will neutralize the excess hydrogen ions in the activated material, making the modified material neutral or weakly alkaline, which is beneficial to improving the compressive strength and service life of the obtained product. In some embodiments of the present application, the alkaline substance includes alkaline solid waste, minerals, alkaline reagents, etc., specifically including but not limited to at least one of carbide slag, steel slag, magnesium slag, calcium hydroxide, sodium hydroxide, etc.; in actual operation, considering cost and environmental protection issues, calcium-based solid waste (such as carbide slag and steel slag) is generally used as an alkaline substance and mixed with the activated material to obtain the modified material.
[0036] In addition, in some embodiments of the present application, the step of mechanically mixing the alkaline substance and the activated material generally includes two stages, namely, a first mechanical mixing and a second mechanical mixing. Specifically, the rotation speed of the first mechanical mixing is 100 r / min~200 r / min, the time is 60 min~90 min, and the mass of the added alkaline substance accounts for 5%~20% of the mass of the lithium slag; the rotation speed of the second mechanical mixing is 250 r / min~400 r / min, the time is 30 min~60 min, and the mass of the added alkaline substance accounts for 2%~4% of the mass of the lithium slag.
[0037] In the first mechanical mixing process, the mixing time is long and the speed is slow. The alkaline substance mainly plays the role of neutralizing excess hydrogen ions. In the neutralization process, mineral phases such as calcium sulfate and aluminum sulfate can be generated, providing active raw materials for the subsequent formation of cementitious mineral phases such as ettringite and hydrated calcium silicate. In the second mechanical mixing process, the mixing time is short and the speed is fast. The alkaline substance can further decompose the undissociated aluminosilicate in the lithium slag to generate active aluminates and silicates, further improving the activity of the modified lithium slag, which is beneficial to the subsequent increase in the lithium slag content in the lithium slag-based composite cementitious material, and can also avoid the phenomenon of consuming the activator in the traditional alkali excitation process mechanism.
[0038] S300, grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material.
[0039] In this step, since the elements such as aluminum, silicon, sulfur, and calcium in the modified powder have been induced and excited, the reaction activity of the modified powder is relatively high, and a lithium slag-based composite cementitious material with high compressive strength can be generated without a large amount of auxiliary materials. For example, in some embodiments of the present application, the mass of the added auxiliary materials can account for 40% to 60% of the mass of the lithium slag in step S100.
[0040] In addition, in some embodiments of the present application, auxiliary materials include but are not limited to at least one of slag, clinker, fly ash or gypsum, especially slag and clinker, which can be combined with modified powder to generate a higher strength cementitious composite material. However, due to the high cost of clinker, in actual operation, considering the cost issue, the auxiliary materials are usually a combination of the above four substances.
[0041] In addition, in the actual production process, auxiliary materials are generally added in two batches during grinding. Specifically, the first batch of fly ash and gypsum is added to ensure that the system has sufficient aluminum, silicon, calcium, and sulfur components, and to keep the system highly active; the second batch of slag and clinker can produce alkaline substances to stimulate the system aluminum silicate, and at the same time generate high-activity cementitious mineral phases such as dicalcium silicate, tricalcium silicate, and calcium aluminosilicate, which react with water to generate high-strength composite cementitious mineral phases such as calcium sulfonate and hydrated calcium silicate, greatly improving the utilization rate of solid waste and reducing the amount of clinker, cement, activator, etc.
[0042] In the first stage of grinding, the speed is usually 200r / min~300r / min, and the time is 30min~60min. Specifically, the speed can be any value of 200r / min, 250r / min, 300r / min, etc., or in the range of any two of the above values, the time can be any value of 30min, 40min, 50min, 60min, etc., or in the range of any two of the above values, and the mass of the added fly ash and gypsum accounts for 5%~20% of the mass of the lithium slag, for example, 5%, 10%, 15%, 20%, etc., or in the range of any two of the above values.
[0043] In the second stage of grinding, the speed is usually 100r / min~200r / min, and the time is 60min~90min. Specifically, the speed can be any value of 100r / min, 150r / min, 200r / min, etc., or in the range of any two of the above values, and the time can be any value of 60min, 70min, 80min, 90min, etc., or in the range of any two of the above values; the mass of the added slag generally accounts for 10%~30% of the mass of the lithium slag, and specifically can be any value of 10%, 15%, 20%, 25%, 30%, etc., or in the range of any two of the above values; the mass of the added clinker generally accounts for 2%~10% of the mass of the lithium slag, and specifically can be any value of 2%, 4%, 6%, 8%, 10%, etc., or in the range of any two of the above values.
[0044] The lithium slag-based composite cementitious material obtained by the preparation method of the present application is an active powder. Unlike traditional geopolymers, the lithium slag-based composite cementitious material of the present application has a wider application range and a larger transportation radius. It can well replace 52.5 or even 62.5 cement and can be widely used in building materials, concrete, products, ecological restoration, mine filling, roadbed materials, etc. Moreover, the compressive strength of the lithium slag-based composite cementitious material obtained by the preparation method of the present application conforms to the corresponding regression equation, and the required mechanical properties can be obtained by adjusting the material parameters.
[0045] The features and performance of the present application are further described in detail below in conjunction with the examples. In the specific examples of the present application, unless otherwise specified, the pH values and hydrogen ion concentrations are based on the values measured at 25°C. In addition, the compressive strength test in the present application is carried out in accordance with the GB50107 standard.
[0046] Example 1
[0047] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0048] (1) A sulfuric acid solution with a hydrogen ion concentration of 8 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 10% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 150 r / min and the ball milling time is 60 min; the rotation speed of the second activation stage is 400 r / min and the ball milling time is 90 min.
[0049] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 4% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 200 r / min for 90 min; the mass of the carbide slag added in the second batch accounts for 2.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 400 r / min for 60 min.
[0050] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. In the first grinding stage, the rotation speed is 300 r / min, the time is 60 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 10% and 10% of the mass of the lithium slag in step (1) respectively; in the second grinding stage, the rotation speed is 200 r / min, the time is 90 min, and the auxiliary materials are slag and clinker, whose mass accounts for 25% and 6% of the mass of the lithium slag in step (1) respectively.
[0051] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 25.48 MPa, the 7-day compressive strength can reach 46.54 MPa, and the 28-day compressive strength can reach 72.83 MPa.
[0052] Example 2
[0053] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0054] (1) Sulfuric acid with a hydrogen ion concentration of 5 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 20% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 100 r / min and the ball milling time is 50 min; the rotation speed of the second activation stage is 300 r / min and the ball milling time is 75 min.
[0055] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 8 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 4% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 200 r / min for 90 min; the mass of the carbide slag added in the second batch accounts for 3% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 350 r / min for 40 min.
[0056] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. In the first grinding stage, the speed is 200 r / min, the time is 60 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 10% and 15% of the mass of the lithium slag in step (1) respectively; in the second grinding stage, the speed is 100 r / min, the time is 90 min, and the auxiliary materials are slag and clinker, whose mass accounts for 20% and 4% of the mass of the lithium slag in step (1) respectively.
[0057] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 22.47 MPa, the 7-day compressive strength can reach 41.28 MPa, and the 28-day compressive strength can reach 67.51 MPa.
[0058] Example 3
[0059] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0060] (1) A sulfuric acid solution with a hydrogen ion concentration of 36 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 2% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 150 r / min and the ball milling time is 60 min; the rotation speed of the second activation stage is 400 r / min and the ball milling time is 90 min.
[0061] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 10 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 3.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 200 r / min for 90 min; the mass of the carbide slag added in the second batch accounts for 2% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 400 r / min for 60 min.
[0062] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. During the first grinding stage, the rotation speed is 250 r / min, the time is 40 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 5% and 10% of the mass of the lithium slag in step (1) respectively; during the second grinding stage, the rotation speed is 200 r / min, the time is 75 min, and the auxiliary materials are slag and clinker, whose mass accounts for 15% and 10% of the mass of the lithium slag in step (1) respectively.
[0063] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 20.38 MPa, the 7-day compressive strength can reach 38.76 MPa, and the 28-day compressive strength can reach 63.71 MPa.
[0064] Example 4
[0065] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0066] (1) A sulfuric acid solution with a hydrogen ion concentration of 15 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 6% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 140 r / min and the ball milling time is 45 min; the rotation speed of the second activation stage is 330 r / min and the ball milling time is 60 min.
[0067] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 180 r / min and the time is 70 min; the mass of the carbide slag added in the second batch accounts for 2.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 360 r / min and the time is 40 min.
[0068] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. During the first grinding stage, the rotation speed is 270 r / min, the time is 35 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 5% and 15% of the mass of the lithium slag in step (1) respectively; during the second grinding stage, the rotation speed is 180 r / min, the time is 80 min, and the auxiliary materials are slag and clinker, whose mass accounts for 10% and 10% of the mass of the lithium slag in step (1) respectively.
[0069] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 23.79 MPa, the 7-day compressive strength can reach 43.84 MPa, and the 28-day compressive strength can reach 70.68 MPa.
[0070] Example 5
[0071] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0072] (1) A sulfuric acid solution with a hydrogen ion concentration of 25 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 3.5% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 110 r / min and the ball milling time is 35 min; the rotation speed of the second activation stage is 360 r / min and the ball milling time is 55 min.
[0073] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 6% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 160 r / min and the time is 85 min; the mass of the carbide slag added in the second batch accounts for 2% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 340 r / min and the time is 55 min.
[0074] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. During the first grinding stage, the rotation speed is 270 r / min, the time is 35 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 10% and 6% of the mass of the lithium slag in step (1), respectively; during the second grinding stage, the rotation speed is 180 r / min, the time is 80 min, and the auxiliary materials are slag and clinker, whose mass accounts for 25% and 6% of the mass of the lithium slag in step (1), respectively.
[0075] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 21.37 MPa, the 7-day compressive strength can reach 41.52 MPa, and the 28-day compressive strength can reach 69.46 MPa.
[0076] Example 6
[0077] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0078] (1) A sulfuric acid solution with a hydrogen ion concentration of 12 mol / L is uniformly mixed with lithium slag, and then activated by mechanical activation to obtain an activated material, wherein the mass of the sulfuric acid solution accounts for 7% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 125 r / min and the ball milling time is 45 min; the rotation speed of the second activation stage is 390 r / min and the ball milling time is 70 min.
[0079] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 4.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 170 r / min and the time is 65 min; the mass of the carbide slag added in the second batch accounts for 2.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 390 r / min and the time is 30 min.
[0080] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. In the first grinding stage, the rotation speed is 280 r / min, the time is 40 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 5% and 10% of the mass of the lithium slag in step (1) respectively; in the second grinding stage, the rotation speed is 200 r / min, the time is 60 min, and the auxiliary materials are slag and clinker, whose mass accounts for 30% and 3% of the mass of the lithium slag in step (1) respectively.
[0081] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 23.64 MPa, the 7-day compressive strength can reach 43.95 MPa, and the 28-day compressive strength can reach 71.82 MPa.
[0082] Example 7
[0083] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0084] (1) A nitric acid solution with a hydrogen ion concentration of 10 mol / L is uniformly mixed with lithium slag, and then activated by a mechanical activation method to obtain an activated material, wherein the mass of the nitric acid solution accounts for 8% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 140 r / min and the ball milling time is 35 min; the rotation speed of the second activation stage is 345 r / min and the ball milling time is 80 min.
[0085] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 165 r / min and the time is 60 min; the mass of the carbide slag added in the second batch accounts for 2% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 330 r / min and the time is 40 min.
[0086] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. During the first grinding stage, the rotation speed is 260 r / min, the time is 80 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 5% and 25% of the mass of the lithium slag in step (1) respectively; during the second grinding stage, the rotation speed is 175 r / min, the time is 45 min, and the auxiliary materials are slag and clinker, whose mass accounts for 15% and 7% of the mass of the lithium slag in step (1) respectively.
[0087] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 20.92 MPa, the 7-day compressive strength can reach 41.58 MPa, and the 28-day compressive strength can reach 69.38 MPa.
[0088] Example 8
[0089] This embodiment provides a lithium slag-based composite gelling material and a preparation method thereof, the preparation method specifically comprising the following steps:
[0090] (1) A nitric acid solution with a hydrogen ion concentration of 12 mol / L is uniformly mixed with lithium slag, and then activated by a mechanical activation method to obtain an activated material, wherein the mass of the nitric acid solution accounts for 6% of the mass of the lithium slag. The activation treatment is divided into a first activation treatment stage and a second activation treatment stage, wherein the rotation speed of the first activation stage is 100 r / min and the ball milling time is 50 min; the rotation speed of the second activation stage is 380 r / min and the ball milling time is 85 min.
[0091] (2) The carbide slag is divided into two batches and slowly added to the activated powder of step (1) and mechanically mixed. After sufficient mixing, a modified material with a pH of 7 is obtained, which is then dried to obtain a modified powder. The mass of the carbide slag added in the first batch accounts for 3.5% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 185 r / min and the time is 75 min; the mass of the carbide slag added in the second batch accounts for 4% of the mass of the lithium slag, and the stirring speed during mechanical mixing is 360 r / min and the time is 50 min.
[0092] (3) Grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite cementitious material. The grinding process is divided into a first grinding stage and a second grinding stage. During the first grinding stage, the rotation speed is 280 r / min, the time is 65 min, and the auxiliary materials are fly ash and graphite, whose mass accounts for 5% and 30% of the mass of the lithium slag in step (1) respectively; during the second grinding stage, the rotation speed is 180 r / min, the time is 35 min, and the auxiliary materials are slag and clinker, whose mass accounts for 20% and 5% of the mass of the lithium slag in step (1) respectively.
[0093] The 3-day compressive strength of the lithium slag-based composite cementitious material of this embodiment can reach 22.58 MPa, the 7-day compressive strength can reach 42.79 MPa, and the 28-day compressive strength can reach 72.17 MPa.
[0094] Example 9
[0095] This embodiment provides a lithium slag-based composite cementitious material and a preparation method thereof. The main difference between the preparation method of the lithium slag-based composite cementitious material and that of the embodiment 1 is that fly ash is not added in step (3).
[0096] The 3-day compressive strength of the lithium slag-based composite cementitious material in this embodiment is 17.85 MPa, the 7-day compressive strength is 31.78 MPa, and the 28-day compressive strength is 57.48 MPa; its strength is lower than that in Example 1. This is because no fly ash is added, which will lead to poor fluidity of the system, poor mixing effect of the system, and uneven system on the one hand; on the other hand, the aluminum silicon resources in the fly ash will be lacking, which will affect the formation of the calcium sulfide cementitious mineral phase, thereby causing the performance of the cementitious material to deteriorate.
[0097] Example 10
[0098] This embodiment provides a lithium slag-based composite cementitious material and a preparation method thereof. The main difference between the preparation method and that of Embodiment 1 is that no clinker is added in step (3).
[0099] The 3-day compressive strength of the lithium slag-based composite cementitious material in this embodiment is 18.72 MPa, the 7-day compressive strength is 34.35 MPa, and the 28-day compressive strength is 55.89 MPa; its strength is lower than that in Example 1. This is because the clinker contains highly active minerals such as dicalcium silicate, calcium aluminate, and calcium hydroxide. The lack of induction of highly active clinker makes it difficult to form important raw materials for cementitious products such as hydrated calcium silicate and calcium aluminate during the hydration reaction, resulting in poor performance of the cementitious material.
[0100] Comparative Example 1
[0101] This comparative example provides a lithium slag-based composite cementitious material and a preparation method thereof. The main difference between the preparation method and that of Example 1 is that: in step (1), no acid solution is added, and mechanical activation treatment is directly performed.
[0102] The 3-day compressive strength of the lithium slag-based composite cementitious material in this comparative example is 9.85 MPa, the 7-day compressive strength is 15.74 MPa, and the 28-day compressive strength is 27.32 MPa.
[0103] In this comparative example, the ball milling process is directly carried out without adding inorganic acid, and the structure of lithium slag aluminum silicate does not change at all, and its reaction activity does not change. Its strength performance can only be improved by the hydration of slag and clinker, resulting in poor performance of the cementitious material.
[0104] Comparative Example 2
[0105] This comparative example provides a lithium slag-based composite cementitious material and a preparation method thereof. The steps thereof are different from those of Example 1 in that after the activated material is obtained by activation treatment with an acid solution, step (2) is not performed, and the activated material is directly dried and mixed with the auxiliary material.
[0106] The 3-day compressive strength of the lithium slag-based composite cementitious material in this comparative example is 12.74 MPa, the 7-day compressive strength is 18.63 MPa, and the 28-day compressive strength is 31.46 MPa.
[0107] In this comparative example, the activated material obtained in step (1) was not neutralized, resulting in most of the high-activity slag and clinker participating in the neutralization reaction, and the high-activity components in the clinker and slag were destroyed, resulting in poor subsequent hydration effect, thereby resulting in poor performance of the cementitious material.
[0108] Comparative Example 3
[0109] This comparative example provides a lithium slag-based composite gelling material and a preparation method thereof. The difference between the preparation method of the lithium slag-based composite gelling material and Example 1 is that after adding alkaline substances such as carbide slag and the activated material in step (2) and mixing them, the pH of the modified material obtained is 11.
[0110] The 3-day compressive strength of the lithium slag-based composite cementitious material in this comparative example is 14.26 MPa, the 7-day compressive strength is 20.36 MPa, and the 28-day compressive strength is 34.85 MPa.
[0111] In this comparative example, the activated slag obtained in step (1) is neutralized. However, when the alkaline substance is excessive, the alkalinity of the system is too high, the active calcium content is too high, and it is easy to expand, resulting in cracking of the material in the later stage, thereby resulting in poor performance of the cementitious material.
[0112] In summary, in the preparation method provided by the present invention, lithium slag is used as a raw material, and proton acid activation and mechanical coupling are adopted to realize the depolymerization activation of inert aluminosilicates to generate active aluminates and silicates, which not only improves the volcanic ash activity of lithium slag, but also aluminum-calcium impurities can be used in situ to form aluminum-calcium chemical activators, solving the problem of low reaction activity of lithium slag. In addition, by adding alkaline substances, on the one hand, excess sulfuric acid can be neutralized to ensure the stability of the gelling system, and on the other hand, the deep dissociation of aluminosilicates can be further promoted to improve the activity, so as to achieve the stability of the gelling system and greatly improve the activity of lithium slag; finally, by adding fly ash, gypsum, slag, clinker and other auxiliary materials in batches, the system aluminum, silicon, sulfur, calcium and other elements are induced to generate gelling materials, and the compressive strength can reach the requirements of cement of 52.5 or even 62.5 grades, while avoiding the consumption of alkali activators, greatly reducing the amount of clinker and cement, shortening the process flow, and reducing production costs.
[0113] The above are only embodiments of the present application and are not intended to limit the scope of protection of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for preparing a lithium slag-based composite gelling material, characterized in that: It includes the following steps: S100, mixing lithium slag with an inorganic acid solution and performing activation treatment to obtain an activated material, wherein the components of the lithium slag include aluminosilicate and calcium oxide; S200, mechanically mixing the alkaline substance and the activated material to obtain a modified material, wherein the pH of the modified material is 7 to 10, and then drying the modified material to obtain a modified powder; S300, grinding the modified powder and auxiliary materials to obtain a lithium slag-based composite gelling material; In step S200, the alkaline substance includes at least one of carbide slag, steel slag, magnesium slag, calcium hydroxide or sodium hydroxide; The auxiliary material includes at least one of slag, clinker, fly ash or gypsum; the mass of the added auxiliary material accounts for 40% to 60% of the mass of the lithium slag.
2. The method for preparing the lithium slag-based composite gelling material according to claim 1, characterized in that: Based on the mass of the lithium slag, the mass content of aluminum oxide in the aluminosilicate is 10% to 20%, the mass content of silicon dioxide in the aluminosilicate is 30% to 60%, and the mass content of calcium oxide is 5% to 30%.
3. The method for preparing the lithium slag-based composite gelling material according to claim 1 or 2, characterized in that: The lithium slag includes at least one of lepidolite smelting slag and spodumene smelting slag.
4. The method for preparing the lithium slag-based composite gelling material according to claim 1, characterized in that: It satisfies at least one of the following conditions: (1) In the inorganic acid solution, the inorganic acid includes at least one of sulfuric acid or nitric acid; (2) In the inorganic acid solution, the hydrogen ion concentration is 5 mol / L to 36 mol / L; (3) The mass of the inorganic acid solution accounts for 5% to 20% of the mass of the lithium slag.
5. The method for preparing the lithium slag-based composite gelling material according to claim 1, characterized in that: In step S100, the activation treatment is performed using a mechanical activation method.
6. The method for preparing the lithium slag-based composite gelling material according to claim 1, characterized in that: The step of mechanically mixing the alkaline substance and the activated material comprises a first mechanical mixing and a second mechanical mixing in sequence; The rotation speed of the first mechanical mixing is 100r / min~200r / min, the time is 60min~90min, and the mass of the added alkaline substance accounts for 5%~20% of the mass of the lithium slag; the rotation speed of the second mechanical mixing is 250r / min~400r / min, the time is 30min~60min, and the mass of the added alkaline substance accounts for 2%~4% of the mass of the lithium slag.
7. The method for preparing the lithium slag-based composite gelling material according to claim 1, characterized in that: It satisfies at least one of the following conditions: (1) The gypsum includes at least one of desulfurized gypsum, anhydrite, phosphogypsum or fluorinated gypsum; (2) The fly ash comprises at least one of fluidized bed fly ash and pulverized coal furnace fly ash; (3) The clinker includes at least one of silicate clinker, aluminate clinker or sulphoaluminate clinker.
8. A lithium slag-based composite gelling material, which is prepared by the preparation method of the lithium slag-based composite gelling material according to any one of claims 1 to 7.
Citation Information
Patent Citations
A clinker-free lithium slag composite cementitious material
CN106116189B
A lithium slag gelling material and preparation method thereof
CN117756487B
Method for preparing high-purity calcium sulfate by desulfurizing and decalcifying lithium slag
CN118026239A